A report on a case of Giardia duodenalis (Journal of Pathology of Nepal, 2017)
ABSTRACTGiardia is caused by protozoa, Giardia lamblia. It is one of the most common causes of water born or food born diarrhea and it has a worldwide distribution. The prevalence is approximately 20-30% in developing countries. Giardia duodenalis is the most commonly reported intestinal protozoan in humans mainly affecting children. The infection is usually associated with malabsorption, weight loss and growth retardation.We report a case of four years old boy who presented with diarrhea and malabsorption for last 2 years. Its clinical presentation and histopathological diagnosis on duodenal biopsy is discussed.